Pengaruh Pelatihan Dan Disiplin Kerja Terhadap Kinerja Karyawan PT Saitama Stamping Indonesia Di KIIC - Akbar Saeful Rochman; Sungkono Sungkono; Maman Mulya Karnama (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The research aims to determine how training, work discipline and employee performance at PT Saitama Stamping Indonesia, determine the effect of training on employee performance and the influence of work discipline on employee performance at PT Saitama Stamping Indonesia. The method used is descriptive and verifiative with a population of 420 employees of PT Saitama Stamping Indonesia. A sample of 81 respondents was taken by the Slovin method. Analysis using SEM with the help of SmartPLS. The results showed that training was in the fairly high category, work discipline was in the high category, and employee performance was in the high category. Training has a positive and significant influence on employee performance at PT Saitama Stamping Indonesia and work discipline has a positive and significant influence on employee performance at PT Saitama Stamping Indonesia. Keywords: Training, Work Discipline and Employee Performance.